2020
DOI: 10.1038/s41467-019-13998-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient lateral-structure perovskite single crystal solar cells with high operational stability

Abstract: The power conversion efficiency of perovskite polycrystalline thin film solar cells has rapidly increased in recent years, while the stability still lags behind due to its low thermal stability as well as the fast ion migration along the massive grain boundaries. Here, stable and efficient lateral-structure perovskite solar cells (PSCs) are achieved based on perovskite single crystals. By optimizing anode contact with a simple surface treatment, the open circuit voltage and fill factor dramatically increase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
150
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 50 publications
1
150
0
Order By: Relevance
“…243,244 Due to the low energy barriers to ionic transport in LHPs, the ionic migration is a suspected reason for instability of PSCs. 244,245 It has been reported that metal from the metal contact diffuses to LHP through the HSL. 186,246 Several strategies have been explored to hinder the metalmigration-induced degradation of PSCs.…”
Section: Interfaces Between the Layersmentioning
confidence: 99%
“…243,244 Due to the low energy barriers to ionic transport in LHPs, the ionic migration is a suspected reason for instability of PSCs. 244,245 It has been reported that metal from the metal contact diffuses to LHP through the HSL. 186,246 Several strategies have been explored to hinder the metalmigration-induced degradation of PSCs.…”
Section: Interfaces Between the Layersmentioning
confidence: 99%
“…[ 20,21 ] Very recently, Dong group demonstrated stable and efficient later‐structure perovskite. [ 22 ] An illuminating statistical paper based on the single crystals from the Chen group called for more research activities in this emerging field. [ 23 ]…”
Section: Figurementioning
confidence: 99%
“…The mesoporous device retained more than 70% of its PCE even aer 5000 h of aging, which is the highest reported stability amongst SC-MAPbI 3 solar cells to the best of our knowledge. 22,23 Further trapping of charges will be minimized due to this micro-structural improvement. Negligible changes could be observed in V OC and FF of the mesoporous devices as shown in Fig.…”
Section: Photovoltaic Performancementioning
confidence: 99%